Perceptions of Students Using E-Learning Application in Learning Science - Mulyadi; Ridwan; Baso Intang Sappaile; Lasino; Afif Alfiyanto (Postgraduate, University of Mataram, 2023)
the purpose of this research is to know the implementation of learning using e-learning. This study uses descriptive qualitative research with a phenomenological approach and literature review as reference material. Data collection tools used in this research are observation, interviews, and documentation. This research study focuses on class 2019 students who carry out learning using e-learning applications. Data collected from students were then analyzed using reduction data, presentation data, and verification data. The results of this study are then poured into writing after checking the validity of the data so that the data can be trusted. Triangulation is one of the data validity techniques used in this study. So that the results obtained are that students' perceptions of learning using e-learning are different, namely: students and lecturers do not fully understand the implementation of e-learning; facilities provided by campuses do not support e-learning based learning, such as WiFi and internet quota subsidies; lack of interaction between lecturers and students, and some lecturers have not fully implemented e-learning.